Economic Motives and Willingness of Young People to Participate in Fraud - Dimitrijević, Dragomir; Jovanović, Dejan (Naše gospodarstvo/Our economy, 2022)
Fraud is linked to economic and financial pressures that force people to commit it.Any fraud, regardless of the gender and age of the fraud perpetrators, inevitably leaves a short-term or long-term negative mark on society's economy. Many financial frauds in the past (Enron, WorldCom, Parmalat) have left profound negative consequences on global financial markets. Such "financial strikes" on the financial markets led to financial losses of many companies (not only those in which frauds were committed), the dismissal of many workers, and even the bankruptcy of companies. Successful detection and prevention of fraud imply the harmonious and efficient operation of several factors. One of them understands people’s attitudes towards fraud. It is necessary to understand what motivates an individual to commit fraud and the conditions under which someone would commit fraud. Plenty of resources and time have been invested in understanding the motives for adult fraud, i.e., mature people. Experience has shown that it is much more challenging to educate people of that era about the harmful effects of fraud and thus convince them not to commit fraud. For these reasons, the subject of this paper is the consideration of the attitudes of the younger population towards fraud in Serbia. More precisely, the paper discusses the attitudes of young people aged 18 to 30 regarding motives, pressures, and opportunities to commit fraud, participate in corruption, or offer bribes. The main objective is to indicate the tendency of young people to participate in fraud and examine whether respondents’ gender influences their willingness to participate in fraud. The research results suggest that, according to young people, the main motive why someone would participate in fraud is financial gain and that young people would participate in fraud only if they could get medical intervention sooner. They also believe that fraud is most prevalent in public administration and that men are more prone to fraud than women, but that the influence of gender is very small.